Prevalence and Practice of Unused and Expired Medicine—A Community-Based Study among Saudi Adults in Riyadh, Saudi Arabia - Samreen, Sana; Mothana, Ramzi A.; Siddiqui, Nasir A.; Wajid, Syed (BioMed research international, 2020)
Purpose. The objective of the current study was to determine the prevalence and practice of unused and expired medicine among Saudi adults. Subjects and Methods. The study used cross-sectional web-based design to collect the data, over a period of 4 months among people who are living in Riyadh, Saudi Arabia. Results. A total of 337 questionnaires were obtained during the study period. The majority of respondents were university graduates n=251 (74.7%). The prevalence of unused medicine was n=301 (89.3%). The most commonly used drugs were nonsteroidal anti-inflammatory drugs n=272 (80.7%) and antibiotics n=164 (48.7%). Of the participants, 186 (55.2%) checked the expiry date of the medicine before they purchase. Most of them n=305 (90.5%) obtained medicine through prescription. About n=219 (65%) of them keep the medicine until it expired; 48.1% throw away in the household garbage while only 18 (5.4%) of the respondents said to give it back to the medical store. Conclusion. The study revealed a high prevalence of unused medications among Saudi community. However, the disposable practice among the Saudi community was inadequate. Increasing awareness through education programs about proper disposable guidelines is necessary for controlling the medication wastage.